2000
DOI: 10.1080/11250000009356374
|View full text |Cite
|
Sign up to set email alerts
|

A key to the lichens of Terra Nova Bay (Victoria Land, Continental Antarctica)

Abstract: After a brief summary of previous Italian lichenological research in Antartica, a key is provided for the identification of the 57 species of lichens and lichenicolous fungi which were hitherto recorded from the Terra Nova Bay area (Victoria Land, Continental Antarctica). The key is based on the analysis of the samples collected during the Italian Antarctic expeditions, and preserved in the TSB lichen herbarium. Due to the high incidence of broadranging, often bipolar or subcosmopolitan species, the lichen flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 4 publications
4
47
0
Order By: Relevance
“…() reported c. 30 species from Casey and Davies stations, also at 66°S. Perhaps the richest place studied in the Ross Sea area so far is Edmonson Point in Terra Nova Bay, with 56 species (Castello & Nimis, ). Thus, the number of lichens found in our study is close to the average figure found on other lichen diversity studies in continental Antarctica.…”
Section: Discussionmentioning
confidence: 99%
“…() reported c. 30 species from Casey and Davies stations, also at 66°S. Perhaps the richest place studied in the Ross Sea area so far is Edmonson Point in Terra Nova Bay, with 56 species (Castello & Nimis, ). Thus, the number of lichens found in our study is close to the average figure found on other lichen diversity studies in continental Antarctica.…”
Section: Discussionmentioning
confidence: 99%
“…Lichens were identified using the key by Castello [33]. All data concerning the sampling sites and the identifications are reported in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Short taxo− nomic notes are provided for selected species and distribution of newly reported taxa is discussed in two categories: world distribution in case of the species new to the Antarctic and Antarctic distribution in case of the species new to the VL area. Information on distribution of other species in VL is available in Castello (2003a) and in the continuously updated on−line database VICTORIA (Castello 2003b;Castello et al 2006).…”
Section: Methodsmentioning
confidence: 99%
“…The re− corded flora comprises 57 lichens, 11 mosses, one liverwort and various species of algae and cyanobacteria (Castello 2003a, b;Cannone 2004;Adams et al 2006). Al− though it seems very poor in species, VL supports some of the most diverse vegeta− tion on the continental Antarctic and several types of plant communities are found in this region (Longton 1973;Castello and Nimis 1995;Cannone and Seppelt 2008).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation